Epidemiology of selected respiratory diseases and their impacts on smallholder pig production systems in Lira District, Uganda - Oba, Peter (Makerere University, 2023)
Respiratory diseases contribute significant economic losses to the swine industry globally. In Uganda, no detailed studies on pig respiratory pathogens have been undertaken previously. This doctoral thesis aimed to fill knowledge gaps on epidemiology of important respiratory pathogens, gastro-intestinal (GIT) parasites and their economic impacts on smallholder pig production systems in Uganda. The studies were conducted in Lira district from October 2018 to September 2019. Four respiratory pathogens of economic importance in pigs including porcine reproductive and respiratory syndrome virus (PPRSv), porcine circovirus type 2 (PCV2), Mycoplasma hyopneumoniae (M. hyo) and Actinobacillus pleuropneumoniae (App) were studied. The first study was a desk systematic review on status and gaps of research on swine respiratory pathogens in Africa. This was followed by three cross-sectional studies: prevalence and risk factors for respiratory co-infections, a slaughter slab survey which correlated serology to 4 selected respiratory pathogens and pneumonia lesions and identify PRRSv genotypes. Tissue and blood samples were collected from pigs and used for genotypying PRRSv and to determine exposure to respiratory pathogens using ELISA assays, respectively. A mixed effects model was fitted to quantify economic losses due to exposure of pigs to respiratory pathogens and GIT parasites. Results highlighted major knowledge, information gaps on epidemiology, and economic impacts of the 4 studied pathogens reported in pigs in Africa. We found that there was dual circulation of both PRRSv PRRSv-1 and PRRSv-2 in Lira district with type 1 more predominant. A high prevalence and severity of pneumonia forms (17.4 – 74.2%) in slaughtered pigs was observed. The model showed that a grower pig in a given farm exposed to PRRSv and Ascaris spp. infection had significantly lower average daily weight gain by 18.5 and 23.7 grams/pig/day respectively, compared to a similar unexposed pig. Monetary losses encountered by farmers due to PRRSv and Ascaris spp. infection amounted to USD 7.12 and USD 9.16 respectively, per pig during 200 days of fattening. In conclusion, these findings strengthened evidence of the role of housing, hygiene and biosecurity in reducing disease incidence in herds. The most important respiratory pathogens were PPRSv, App, Ascaris spp. and risk factors were use of murram as floor type, poor hygiene, biosecurity practices, and concurrent GIT parasite infestations. Associations between serology and lung lesions suggests their potential role in lung disease precipitation. Farmers should pay close attention to proper housing, hygiene, biosecurity, wastes management and parasite control and limiting contacts with outside pigs. The findings from this study shall inform national policy in Uganda.